Porcine circovirus 2d associated with stillborn mummified foetus of pig - H B, VIDYARANI; DAS, TARENI; SAIKUMAR, G (The Indian Journal of Animal Sciences, 2024)
Recurrent occurrence of stillborn piglets was noticed along with live births during farrowing in pigs in an organized pig farm of Uttar Pradesh. On detailed post mortem examination, externally, the foetus was found to be partially dehydrated and dark brown in colour with shrunken eyes. Internally, visceral organs including lungs, heart, kidneys, liver, spleen and intestine were partially dehydrated and dark brown in colour. Upon molecular investigation, the pooled tissue samples were found positive for porcine circovirus 2 (PCV2) infection using PCR technique and further confirmed the PCV2d genotype by DNA sequencing. Other most possible infections including porcine parvoviral infection (PPV), PCV3 and porcine respiratory and reproductive syndrome virus infection (PRRS) were found negative using PCR and RT-PCR techniques, respectively. This result is suggestive of role of PCV2d as a possible etiological agent to cause stillbirth and mummification of porcine foetuses.